2005
DOI: 10.1089/sur.2005.6.233
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in the Intensive Care Unit: No Longer Just a Marker of Illness Severity

Abstract: A number of human studies have demonstrated improved outcomes in critically ill patient populations receiving insulin therapy with a target of euglycemia, suggesting at least part of the benefit of this therapy is normal blood sugar and not the effects of insulin. An important population not studied to date is patients in the medical ICU. However, aggressive control of hyperglycemia now remains an important component of care for all surgical patients in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 79 publications
0
19
1
Order By: Relevance
“…However, hyperglycemia may harm immunity through non-enzymatic glycosylation of circulating immunoglobulins [42,43]. In our study, no significant correlation was observed between glucose levels and cellular, innate immunity, suggesting higher levels of glucose in the HBM hamsters had no effect on immune function in contrast with the LBM hamsters.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, hyperglycemia may harm immunity through non-enzymatic glycosylation of circulating immunoglobulins [42,43]. In our study, no significant correlation was observed between glucose levels and cellular, innate immunity, suggesting higher levels of glucose in the HBM hamsters had no effect on immune function in contrast with the LBM hamsters.…”
Section: Discussioncontrasting
confidence: 74%
“…Glucose plays a role in normal survival and function of lymphocytes, and glucose uptake and glycolysis increase in T cells during an immune response [40,41], whereas hyperglycemia reduces immune function [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Early hyperglycemia is a common metabolic feature following exposure to bacterial endotoxins (5). It is known to contribute to poor immune function, oxidative stress, increased susceptibility to infectious complications, impaired recovery of organ failure, and endothelial and myocardial dysfunction (6,7). In critically ill patients, hyperglycemia is not only a marker of illness severity but also a predictor of a poor clinical outcome (7).…”
Section: Lipopolysaccharides-mediatedmentioning
confidence: 99%
“…It is known to contribute to poor immune function, oxidative stress, increased susceptibility to infectious complications, impaired recovery of organ failure, and endothelial and myocardial dysfunction (6,7). In critically ill patients, hyperglycemia is not only a marker of illness severity but also a predictor of a poor clinical outcome (7). Although effective glucose control through aggressive insulin therapy has been reported to improve clinical outcome, it remains unclear to what extent insulin infusion may in fact be beneficial (8).…”
Section: Lipopolysaccharides-mediatedmentioning
confidence: 99%
“…There are many metabolic disturbances during severe sepsis and septic shock, and one of the most striking is hyperglycaemia (27). Intensive insulin therapy became popular in the intensive care unit (ICU) after research reporting its effectiveness on glycaemic control (28,29).…”
Section: Discussionmentioning
confidence: 99%